Principais causas das a????es judiciais envolvendo os hospitais p??blicos no munic??pio de S??o Paulo - Orita, Marcos Rog??rio (2018)
Public management alone is complex. From the constitutional point of view, every public administration must respect the principles of legality, impersonality, morality, publicity and efficiency. When faced with the management of the public health system complexity becomes more pronounced, as there is another constitutional provision of universal access for all. In this same way, public hospitals face challenges in the management of their budgets, and it is the responsibility of the manager to administer in the best possible way and with the necessary efficiency and effectiveness. Hospital management represents a complexity of decisions involving many departments and skilled manpower. This paper presents a study on the legal cases that affected municipal public hospitals in the city of S??o Paulo. It was possible to identify nineteen hospitals administered directly and indirectly by the municipality, through the Social Health Organizations, which have greater autonomy and control of their accounts by the municipality, when compared to the state management. The research was quantitative, exploratory and documentary and used all the public information available on the website of Tribunal de Justi??a do Estado de S??o Paulo, involving all judgments judged and published in the period of five years, covering 01/01 / 2012 to 12/31/2016. The result reported the existence of 499 (four hundred and ninety-nine) judgments that were classified by subject according to the role made available at the Court. The study revealed the number of judgments involving each year of each of the 19 (nineteen) hospitals surveyed, describing the type of matter brought before the S??o Paulo Judiciary. The research identified 61 (sixty-one) types of subjects cataloged by Tribunal de Justi??a do Estado de S??o Paulo. In view of the large number of subjects and in order to support the administrative management of hospitals, the judgments were categorized into three distinct groups, the first one related to labor issues and reflections resulting from this relationship, which represented 317 judgments (63.53%), of the total, the second in terms of services provided to patients or consumers recorded 122 judgments (24.45%) and the third group in accordance with the practices of the administration found 60 judgments (12.02%) of the total. Finally, this experiment intends to demonstrate to health managers that the information gathered from Tribunal de Justi??a do Estado de S??o Paulo can contribute to the risk management of public hospitals, which could take steps to mitigate or reduce lawsuits, possibly improving the city's budget management of the city of S??o Paulo.